2021
DOI: 10.3389/fmicb.2021.742610
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin-Derived Peptide Val66-Pro85 Is Effective in Limiting Methicillin-Resistant S. aureus Skin Infection

Abstract: Chemerin-derived peptide Val66-Pro85 (p4) restricts the growth of a variety of skin-associated bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). To better understand the antimicrobial potential of chemerin peptide, we compared p4 activity against MRSA in vitro to cathelicidin LL-37, one of the key endogenous peptides implicated in controlling the growth of S. aureus. The efficacy of p4 was also validated in relevant experimental models of skin pathology, such as topical skin infection wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Staphylococcus epidermidis expresses a cysteine protease similar to staphopain B [46], but so far there is no experimental proof for the role of this protease in chemerin cleavage. Interestingly, the chemerin-derived peptide Val 66 -Pro 85 was found to restrict the growth of methicillin-resistant Staphylococcus aureus [47]. Our analysis showed that patients infected with the Gram-positive bacteria Staphylococcus aureus and/or Staphylococcus epidermidis have higher plasma chemerin in comparison to non-infected patients, as well as in comparison to patients with Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 69%
“…Staphylococcus epidermidis expresses a cysteine protease similar to staphopain B [46], but so far there is no experimental proof for the role of this protease in chemerin cleavage. Interestingly, the chemerin-derived peptide Val 66 -Pro 85 was found to restrict the growth of methicillin-resistant Staphylococcus aureus [47]. Our analysis showed that patients infected with the Gram-positive bacteria Staphylococcus aureus and/or Staphylococcus epidermidis have higher plasma chemerin in comparison to non-infected patients, as well as in comparison to patients with Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 69%
“…As a result, it is now known that chemerin, in addition to chemotactic induction in dendritic cells, macrophages and NK cells [ 216 ], plays an important role in angiogenesis [ 217 , 218 ], adipogenesis [ 219 , 220 ], osteoblastogenesis [ 221 ], myogenesis [ 222 ], or glucose homeostasis [ 223 ]. In addition, chemerin plays an important role in inhibiting bacterial growth [ 223 , 224 , 225 ]. Physiologically, chemerin is expressed by many tissues and organs, such as in the lungs, heart, ovaries, kidneys and pancreas but is mainly produced by the liver and white adipose tissue [ 226 , 227 , 228 , 229 ].…”
Section: Chemerinmentioning
confidence: 99%